(untitled) (Conferencea, 2024)
Currently, the real estate market in our country, in particular, the housing and mortgage markets, has high growth rates. In the real estate market, it is important to offer financing methods that are convenient and affordable for the population to effectively meet their demand for housing. In this regard, the main goal of the research is to study the sources and methods of financing and to develop recommendations for improvement. In this thesis, the main financing methods and the indicators related to them, which are currently used by the population in financing housing in Uzbekistan, are analyzed. The analysis materials given in the thesis were also considered in terms of regions. After analyzing the current trends, the necessary conclusions and recommendations are made.